2021
DOI: 10.1007/s00414-021-02590-3
|View full text |Cite
|
Sign up to set email alerts
|

The forensic landscape and the population genetic analyses of Hainan Li based on massively parallel sequencing DNA profiling

Abstract: Due to the formation of the Qiongzhou Strait by climate change and marine transition, Hainan island isolated from the mainland southern China during the Last Glacial Maximum. Hainan island, located at the southernmost part of China and separated from the Leizhou Peninsula by the Qiongzhou Strait, laid on one of the modern human northward migration routes from Southeast Asia to East Asia. The Hlai-language speaking Li minority, the second largest population after Han Chinese in Hainan island, is the direct desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 168 publications
0
9
0
Order By: Relevance
“…The predominantly detected haplogroups were O2-M122 (45.75%), O2a2a1a2-M7 (25.47%), O1a-M119 (10.38%), O1b1a1a-M95 (8.02%), O-M175 (7.08%), and O2a2b1a1-M117 (3.30%), which were determined according to ISOGG, 2019 2 . In addition, a PCA graph was performed among 77 populations ( Wen et al, 2004 ; Gan et al, 2008 ; Li et al, 2008 ; Cai et al, 2011 ; Deng et al, 2013 ; Fan et al, 2018c ; Rowold et al, 2019 ; Luo et al, 2020 ; Fan et al, 2021 ), which were composed of 4,195 individuals in total, including Tai-Kadai, Hmong-Mien, Tibeto-Burman, and Chinese (Southern and Northern Han) populations from Southeast and East Asia, which included three She groups (Fujian, Guangdong Chaoshan, and Guangdong She). From the diagram in Figure 7 , the first and second principal components could explain 33.07% of the total variances.…”
Section: Resultsmentioning
confidence: 99%
“…The predominantly detected haplogroups were O2-M122 (45.75%), O2a2a1a2-M7 (25.47%), O1a-M119 (10.38%), O1b1a1a-M95 (8.02%), O-M175 (7.08%), and O2a2b1a1-M117 (3.30%), which were determined according to ISOGG, 2019 2 . In addition, a PCA graph was performed among 77 populations ( Wen et al, 2004 ; Gan et al, 2008 ; Li et al, 2008 ; Cai et al, 2011 ; Deng et al, 2013 ; Fan et al, 2018c ; Rowold et al, 2019 ; Luo et al, 2020 ; Fan et al, 2021 ), which were composed of 4,195 individuals in total, including Tai-Kadai, Hmong-Mien, Tibeto-Burman, and Chinese (Southern and Northern Han) populations from Southeast and East Asia, which included three She groups (Fujian, Guangdong Chaoshan, and Guangdong She). From the diagram in Figure 7 , the first and second principal components could explain 33.07% of the total variances.…”
Section: Resultsmentioning
confidence: 99%
“…The Hainan Li, inhabiting in the south of Hainan island, is a relatively isolated minority group in China, which is beneficial to clarify the exquisite population structure and develop specific genetic markers for subpopulations in the forensic genetic field ( Liu et al, 2020b ; Fan et al, 2021a ). Hence, a total of 279 healthy Hainan Li individuals were collected for forensic evaluations of 57 A-InDel loci in EAIS.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the UAIS could supply additional information for the paternity tests. The Hainan Li, inhabiting in the south of Hainan island, is a relatively isolated minority group in China, which is beneficial to clarify the exquisite population structure and develop specific genetic markers for subpopulations in the forensic genetic field (Liu et al, 2020b;Fan et al, 2021a (mean He: 0.4666 ± 0.0560). Moreover, the CPE and CPD of the 57 A-InDels in the Hainan Li group was 0.999965 and 1-1.32 × 10 -23 , which demonstrated that the EAIS have good performances for individual identification and paternity test in the Hainan Li group (Table 2).…”
Section: Details Of the Novel Typing System And Distinct A-indel Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of massive parallel sequencing (MPS) technology [13][14][15][16][17][18][19][20][21][22][23][24], emerging microhaplotypes (i.e., microhaps or MHs, generally <200 bp and consisting of two or more closely linked single nucleotide polymorphisms (SNPs) with three or more allelic combinations [7,25,26]) exhibit promising characteristics for further enhancing the deconvolution of DNA mixtures. MHs present some advantages over standard STRs: (1) a multiallelic nature and the absence of STR structures, which prevents Taq polymerase slippage and stutter peak generation; (2) balanced PCR amplification due to the similar lengths of MH amplicons (preferential PCR amplification for shorter alleles commonly occurs with STRs); and (3) lower mutation rates than STRs.…”
Section: Introductionmentioning
confidence: 99%